2007
DOI: 10.1093/aje/kwm265
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Reporting of Menstrual Cycle Length

Abstract: There are many studies based on self-reported menstrual cycle length, yet little is known about the validity of this measure. The authors used data collected in 1990 from 352 women born in Chicago, Illinois, aged 37-39 years. Women reported their usual cycle length and behavioral and reproductive characteristics at study enrollment and then completed daily menstrual diaries for up to 6 months. The authors compared this observed cycle length (geometric mean) with the reported length by using kappa coefficients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(100 citation statements)
references
References 17 publications
2
94
2
2
Order By: Relevance
“…nurses in the similar NHS I and NHS II were shown to report health data accurately for several medical conditions (31,32). Previous studies that have investigated the accuracy of self-reported menstrual cycle length by comparing initial self-reported "usual" length with prospective diaries, however, Jukic et al (33) and Small et al (34) reported that 21% of cycle length categories were misclassified.…”
Section: Lawson Et Almentioning
confidence: 99%
“…nurses in the similar NHS I and NHS II were shown to report health data accurately for several medical conditions (31,32). Previous studies that have investigated the accuracy of self-reported menstrual cycle length by comparing initial self-reported "usual" length with prospective diaries, however, Jukic et al (33) and Small et al (34) reported that 21% of cycle length categories were misclassified.…”
Section: Lawson Et Almentioning
confidence: 99%
“…Other studies have attempted to time specimen collection to key hormonal events based on self-reported cycle length or cycle day or the assumption that the luteal phase is 14 days [23][24][25], but these methods assume that women can reliably report their cycle length or that the timing of hormonal fluctuations is the same across women, both of which are unlikely to be true [26][27][28][29][30]. The 'gold standard' is daily collection of first-morning urine specimens, which ensures that critical hormone windows are captured if compliance is adequate, but the protocol is burdensome, which affects recruitment and compliance.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have suggested that retrospective self-reports of menstrual history are prone to have errors [20] with volatile accuracy between diary records and retrospectively recalled menstrual history. [21] Second, hormones such as estrogen, testosterone, sex hormonebinding globulin, follicle-stimulating hormone, and luteinizing hormone that may affect the associations between body fat and menstrual cycle characteristics were not examined, nor we were able to find whether women with irregular or variable cycles were anovulatory or oligo-ovulatory. A study has reported that obese women have increased estrogen, luteinizing hormone levels, or an increased ratio of androgen to estrogen.…”
Section: Discussionmentioning
confidence: 99%